Dakon Koper Media of the Least Common Multiple and Greatest Common Divisor Materials for the Elementary School Students - Suwandayani, Beti Istanti; Ekowati, Dyah Worowirastri; Fadillah, Ayu Nur (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2020)
The Program for International Student Assessment (PISA) in 2018 showed that elementary school students' math, literacy, and science skills were poor. These problems occurred due to a lack of understanding and memorization of multiplication. They are considered difficult for students to calculate the results of the least common multiple and greatest common divisor. Thus, the development of learning media in mathematics are needed. The developed media was Dakon Koper. The purpose of this study was to develop Dakon Koper media in thematic learning. This research was a development research by implementing the ADDIE model which consisted of analysis, design, development, implementation, and evaluation. The subjects of this study were the fourth-grade elementary school students. The developed media's feasibility had been determined through a validation questionnaire filled by media, material, and learning experts. Student response questionnaires were used to record students' interest in learning. The expert validation results stated that Dakon Koper was very suitable to be used as a learning medium. The students' questionnaire responses revealed that Dakon Koper was very interesting and useful to support students' learning. Suggestions for the sustainability of this research are product dissemination for learning media in elementary schools.